Soccer clubs and diminishing returns: The case of Paris Saint-Germain - Vincent Hogan; Patrick Massey (University College Dublin, UCD Centre for Economic Research, 2021)
Paris Saint-Germain, one of France's top soccer clubs, was bought by Qatar Sports Investments (QSI) in 2011. Since then the club's expenditure has risen precipitously as have its victories. In this paper we ask whether this represents value for money. We find in fact, that the efficiency of PSG did not deteriorate following the takeover. However, while PSG operated close to the production frontier in terms of converting resources to points, it scored vastly more points than was necessary to win the league. We estimate that PSG spent e140m more than was necessary to win the French league in 2016/17. Since 2011, PSG is estimated to have overspent by up to e600m. This expenditure could be thought as being merely the price of creditable performance at a European Level. We show, however, that it has brought less success than would be expected.
Keywords: Z23; D24; 330; Sports Finance; Productivity